TEACHERS’ READINESS TO IMPLEMENT INQUIRY FOR SCIENCE INSTRUCTION IN ELEMENTARY SCHOOL - Budiastra, A.A. Ketut; Purwoningsih, Tuti (IJRDO- Journal of Educational Research, 2017)
This study aims to know teachers’ readiness in implementing inquiry for scienceinstructions in elementary school. This study implemented dominant less dominantdesign or mixed method. The data was collected using purposive sampling technique.There were 90 elementary school teachers from three regional offices, namelyPangkalpinang, Serang, and Denpasar as respondents for this study. The instruments usedfor this study was a questionnaire as the main data collection, in addition to an interviewand an observation form. 27 teachers from three regional offices were observed using theform for Teacher Performance Assessment Instrument (TPAI). This instrument consistsof two parts, TPAI-1 for assessing the lesson plans and TPAI-2 for assessing theperformance of teachers in actuating the instruction. An in-depth interview wasconducted for 27 elementary school teachers after the observation. On the one hand, theresult shows that only a few teachers can be categorized ready for implementing inquiryfor science instruction. This was concluded from the appraisal of teachers’ preparationand their activities during the instruction process. On the other hand, a large number ofteachers can be categorized not ready to implement inquiry for science instruction. Lackof knowledge and information regarding the importance of inquiry in science instructioncan be mentioned as one of the obstacles in implementing inquiry for science instruction.From this study, it is recommended that inquiry for science instruction needs scienceequipment. However, the most important thing is an inquiry for science instruction needsteachers to change their mindset that science instructions for elementary school must betaught by inquiry.